A Study on the Current Status and Driving Force of Library Marketing in the Digital Age - Jianping Wang; Senqiang Wang; Yanan Liu (Publications)
In the context of the rapid evolution of digital technology and the growing demand for user-centered services, the question of how to effectively implement marketing strategies in libraries has become important in research. This article introduces the theoretical background and development process of domestic and international research on library marketing in the digital era, systematically combs through the current situation of domestic library marketing research, and puts forward the existing deficiencies and problems. Based on the discovery of library marketing strategy research insufficiency and other problems, this paper uses STP theory (segmentation, targeting, and positioning) to conduct a systematic strategy analysis of library operation and management and puts forward countermeasure suggestions for the cross-integration of disciplines, the improvement and optimization of the new theory of library marketing, the integration of STP theory and public library strategy, and the innovation of the research direction.